Uma proposta para o desenvolvimento do índice de avaliação da governança pública (IGovP): instrumento de planejamento e desenvolvimento do estado - Pisa, Beatriz Jackiu (2014)
The public governance concept essence involves different management aspects and among them we can mention: transparency, accountability, ethics, integrity, legality and the possibility of social participation in the public decision-making process addressed to public policy implementation. But, how will we be able to assess the extent to which each federation entity makes a real effort to comply with the public governance principles? Aiming at submitting a consistent assessment proposal, the present study intends to develop a public governance index able to allow the State and the Brazilian society to have a weighed assessment parameter based on governance principles and on the present study indicators to measure addressed public policy effectiveness. The aforementioned tool will contribute to stimulating a solid social control and participation culture, as well as a healthy competition between government entities. As to methodological procedures the research is classified as: applied research, regarding its purpose; comparative, regarding its method; qualitative and quantitative, regarding research approach; exploratory and descriptive, regarding its objectives; and, bibliographic with secondary and indirect sources, regarding its procedures. The research results attest the possibility of creating a public governance assessment index with practical applicability. It would include a series of scores, based on variables and previously established indicators that assigned to federal entities would show their public governance degree.